Physical activity and sports performance among Ethiopianuniversity students: the moderating role of self-esteem and the mediating effect of stress - Yohannes Yusuf; Abdella Borjac, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The primary objective of this study was to investigate the impact of physical activity (PHA) on the academic performance (ACP) of university athletes in Ethiopia. The study also examined the moderating effect of self-esteem (SEE) and the mediating effect of stress control. In order to achieve the objectives of this study, the researchers adopted a quantitative cross-sectional design and employed well-established measurement instruments to evaluate the aforementioned variables. A purposive sampling technique was employed to gather data from a sample of 300 university sports students. The findings obtained from the application of Partial Least Squares (PLS)-Structural Equation Modelling (SEM) indicate a statistically significant and positive correlation between physical health attributes (PHA) and academic performance indicators (ACP). These results underscore the importance of incorporating physical fitness components into the academic curricula designed for university athletes. The study additionally showcased the efficacy of PHA as a stress management strategy by highlighting its notable impact on reducing stress levels. Furthermore, it has been observed that self-efficacy expectations (SEE) play a moderating role in the relationship between perceived academic performance (PHA) and academic career planning (ACP), thus emphasising the potential benefits of interventions aimed at enhancing SEE among students belonging to this particular demographic. The aforementioned observations contribute to a comprehensive understanding of the academic and psychological well-being of Ethiopian university athletes. Furthermore, they offer recommendations for tailored educational strategies aimed at fostering their overall development.